Home environment and burns in children - Agata Kawalec; Krystyna Pawlas (Elsevier, 2020)
Introduction: Most of the burns in children occur at home.The aim: The aim of the study was to determine the relationship between the home environment and chosen parameters of burns in children. Methods: The survey was conducted among caregivers of 200 children (80 girls and 120 boys) who were below 18 years of age and hospitalized due to burns in 5 Polish hospitals. Results: Most often burn injuries occurred in the home environment (85,5%): patient's house (76,5%), neighbor's house (2%), or relative's house (7%). In all, 65% of children were living in the urban areas. Burns were more extensive in children from nonurban areas (p = 0,016). Analyzing of the number of people living with the child in the same household revealed that children living only with their mother were hospitalized longer than children from bigger families (p < 0,05). Children living in coal-heated flats had more extensive burns (p < 0.05) than children who lived in flats where this method of heating was not used. No relationship was found between the assessment of housing conditions, type of water heating methods, and the surface of burn, burn depth, severity of burn, treatment, and the length of hospitalization (p > 0,05). Conclusions: The home environment was related to analyzed parameters of burns in children. The preventive programs should increase the awareness of caregivers about the safe arrangement of housing space.